Synthesis and Characterization of Silver Nanoparticles-Chitosan Beads as Antibacterial Agents - Ayu Safirah; Atik Rismawati; Mohammad Alauhdin; Sri Wardani (Jurnal Kimia Sains dan Aplikasi, 2025)
One of the key innovations in silver nanoparticle (AgNPs) material development is the formation of AgNPs/chitosan beads, which exhibit enhanced properties and broader functionality compared to chitosan or AgNPs alone. In this study, AgNPs/chitosan beads were synthesized using glutaraldehyde as a binding agent and sodium citrate as a reducing agent—both of which are safe and non-toxic, enabling broader applications. The synthesized beads were characterized to assess their chemical and physical properties, including functional groups, morphology, and crystallinity. Characterization results confirmed the successful cross-linking of chitosan by glutaraldehyde, enhancing the material’s physical and chemical strength. The chitosan beads appeared white, while AgNPs/chitosan beads were brownish, with an average bead size of 1.99 mm. X-ray diffraction analysis revealed that the silver in the chitosan beads exhibited a face-centered cubic crystal structure. Antibacterial testing demonstrated that AgNPs/chitosan beads exhibited superior antibacterial activity compared to chitosan beads, attributed to the release of Ag+ ions from the matrix.